Waterville Creates!: Greater than the Sum of Its Arts - O'Neill, Kerill; Rudy, Nate (Maine Policy Review, 2015)
Out of a desire to promote Waterville as a major arts destination, which will foster a robust creative economy for Maine residents and visitors to the state, the city’s largest arts and cultural entities committed to increased collaboration. Waterville Creates! acts as the coordinating entity for arts programming and cultural collaborations in the city. As the city builds recognition as a destination for art, culture, and innovation, Waterville Creates! also works with the city council, local businesses, private foundations, and private colleges to maximize the positive impact on quality of life and economic opportunity for residents. A key goal is to craft meaningful, inclusive, and emotionally intelligent marketing messages to inspire creators, innovators, entrepreneurs, and small business owners to become part of an engaged, intentional, and aesthetically-centered community.